Novel Multivalent Wound-Healing Ointment Provides Bioburden Control and Moisture Management: A Retrospective Registry Data Analysis. (October 2016) - Serena, Thomas; Connell, Heather; McConnell, Sharon; Patel, Keyur; Doner, Bryan; Sabo, Matthew; Miller, Michael; Serena, Laura; Le, Lam T.; Goldsmith, David; Chung, Jane
ABSTRACT: OBJECTIVE: The purpose of this retrospective registry data analysis was to explore the effectiveness of a novel multivalent topical ointment (Terrasil Infection Control Wound Care Ointment; Aspiera Medical, Woonsocket, Rhode Island), containing a patented mineral complex and 0.2% benzethonium chloride in the treatment of nonhealing acute and chronic wounds. DESIGN: Aspiera Medical designed a registry to capture physician experiences and treatment results with Terrasil Infection Control Wound Care Ointment. Physicians were asked to enter deidentified patient data into an online registry. SETTING: Wound clinics in the United States were asked to participate in the registry. PATIENTS: Physicians at 4 wound clinics treated 30 patients (26 of whom completed the treatment) with various chronic wounds that had persisted for an average of 6 months and entered treatment data into the registry. INTERVENTIONS: Patients applied the ointment according to physician orders. Concurrent treatments used by patients included offloading, compression wraps, and dressings, such as collagen and calcium alginate. Patients were treated until complete wound closure or lost to follow-up. MAIN OUTCOME MEASURES: Physicians calculated each patient's percentage wound reduction at each visit. MAIN RESULTS: Thirty patients were entered into the registry. Pretreatment and posttreatment measurements were available for 26 of them. Patients achieved an average surface area reduction of 84% in a mean of 23 days' treatment. CONCLUSION: The antimicrobial and moisturizing ointment studied appears to be effective in promoting wound closure in a variety of acute and chronic wounds. Wounds studied included diabetic foot ulcers, venous leg ulcers, venous stasis ulcers, surgical infections, burns, and insect bites. The results of this registry data analysis will be used to inform planned clinical trials.